Ethnographies of Diagnostic Work
XV, 264 p. 13 illus.
Keywords: This book explores ethnographic studies of diagnostic work in diverse settings. Switching attention from product ('diagnosis') to process ('diagnosing'), it reveals the importance of collaborative, socio-material, technologically augmented practices, exploring the potential of the multi-disciplinary studies presented to inform innovation.